Correlation of the Physician Assistant Education Association End of Rotation Examinations with the Physician Assistant National Certifying Exam. Issue 3 (September 2015) - Massey, Scott; Holmerud, David; Hammond, Jamie; Preston, Teresa; Tipton, Leslie; Rizzolo, Denise
Abstract : Purpose: The purpose of this study was to determine whether student scores on the Physician Assistant Education Association (PAEA) End of Rotation™ subject examinations had a statistically significant relationship with subsequent performance on the Physician Assistant National Certifying Exam (PANCE). The raw scores achieved by students from 3 participating programs were correlated with scores on the PANCE. Methods: Seven 120-question End of Rotation examinations, developed by the PAEA, were administered to students from 3 PA programs (n = 72). The examinations measured knowledge in the following disciplines: family medicine, internal medicine, behavioral medicine, emergency medicine, surgery, OB/GYN, and pediatrics. Results: The mean PANCE score for all programs was 426 (SD = 90) and mean End of Rotation examinations score was 68% (SD = 8.3). The Pearson coefficient between the PANCE and End of Rotation examinations scores was 0.856 ( P < .05). Conclusion: The results of this pilot study suggest that there is a statistically significant correlation between scores on the PAEA End of Rotation examinations and subsequent PANCE performance.